1989
DOI: 10.1159/000174520
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation for Heart Failure Patients

Abstract: Exercise tolerance in patients with normal cardiac function can improve with an exercise program. Controversy exists whether this is also true for patients with congestive heart failure (CHF). The limiting symptoms in patients with CHF are shortness of breath and fatigue. Hemodynamic parameters do not correlate well with exercise capacity in patients with CHF. These symptoms may be more related to factors that cause fatigue during exercise than to hemodynamic parameters or even to changes in pulmonary capillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…(4) Although the need to categorise patients by their haemodynamic features to predict the outcome of exercise training is recognised, [42][43][44] no specific criteria have been established for selection. Scalvini et al have suggested that oxygen uptake of less than 16 ml/kg/min at the peak workload of exercise testing could identify a severe subgroup less likely to benefit from training.…”
Section: Physical Activitymentioning
confidence: 99%
“…(4) Although the need to categorise patients by their haemodynamic features to predict the outcome of exercise training is recognised, [42][43][44] no specific criteria have been established for selection. Scalvini et al have suggested that oxygen uptake of less than 16 ml/kg/min at the peak workload of exercise testing could identify a severe subgroup less likely to benefit from training.…”
Section: Physical Activitymentioning
confidence: 99%
“…Long warm-up and cool-down periods with gentle exercise at a limited workload helps to compensate for an impaired ability to generate a dynamic exercise response, and dynamic exercise is preferred to isometric exercise because isometric exercise can lead to an increase in diastolic pressure and cardiac afterload. 34 Heart rate targets are usually set 10 beats/min less than any notable end point found with cardiopulmonary exercise testing. Cardiac rehabilitation begins with cardiac monitoring especially when severe left ventricular dysfunction is present.…”
Section: Cardiac Rehabilitationmentioning
confidence: 99%
“…Reduced activity capability resulting from a combination of muscular fatigue and dyspnea can be reversed with exercise training (Koch, Douard, & Broustet, 1992), which is now encouraged for patients with CHF to minimize the magnitude of the deconditioning they experience (Garg et al, 1993). CHF patients who receive exercise training improve their exercise capability without adverse effects and with less fatigue (Dubach & Froelicher, 1989; Kostis et al, 1994). Koch et al also noted an estimated 63% improvement in quality of life scores for CHF patients enrolled in an exercise program that had been individually adapted for each patient and that built up a small number of muscle groups at one time.…”
Section: Cardiac Rehabilitationmentioning
confidence: 99%